Effects of Waste Denim Fibre (WDF) on the physical and rheological properties of bitumen - Al-Sabaeei, A. (Institute of Physics Publishing, 2019)
About 15 of the denim jeans are waste materials during the cutting processing in the manufacturing. That is considering a huge waste need to be managed and recycled in a sustainable manner. In this research, waste denim fibre modified binders were prepared at 0.5, 1, 1.5 and 2 concentration of waste denim fibre by weight of bitumen. Effects of waste denim fibre on physical and rheological properties of bitumen were investigated by conducting penetration, softening point, ductility, temperature susceptibility, complex modulus, phase angle and permanent deformation parameters evaluations. Results show that the addition of waste denim fibre reduces the penetration, ductility and temperature susceptibility and increases the softening point of bitumen, which indicating improved permanent deformation resistance of bitumen. Based on dynamic shear rheometer analysis, it was found that, waste denim fibre improved the rheological properties of bitumen from a temperature range of 40°C to 70°C. Furthermore, rutting parameter evaluation indicated that denim fibre modified bitumen has high resistance to rutting due to the enhancement of its elastic behaviour with increased of denim fibre content in the modified binder. It was also noted that 2 WDF is the optimum content for improving the rutting resistance of base bitumen. © 2019 IOP Publishing Ltd. All rights reserved.